Exploring the Intercultural Identity of Slovak-Roma Schoolchildren in the UK - Hryniewicz, Laura; Dewaele, Jean-Marc (Vestnik Rossijskogo universiteta družby narodov. Seriâ Lingvistika, 2017)
There is a significant body of literature about the Roma, but comparatively little exists in which their voices can be heard. This study takes an intercultural perspective to look at the identity negotiations of four self-identifying Roma-Slovak schoolchildren between the ages of 13-14 enrolled at a state academy in Kent. Interviews focused on the role of language in constructing their identities, the perceptions of others and the nature of possible conflicts. The qualitative analyses revealed five themes: Perception of Identity by Others, Adaptability, Aspirations, Self-Perceptions of Identity, and Conflict. Participants’ identities were found to be far more dynamic than the traditional binarized view of the Roma as the ‘other’ (McGarry & Agarin 2014). There is a strong element of ascription by others in terms of the nature of participants’ ethnicity and its relationship to their identity. Both their ethnic and national identity are central in the ways in which they see themselves.